2014
DOI: 10.1021/jp507917u
|View full text |Cite
|
Sign up to set email alerts
|

Excited-State Proton and Charge Transfer in Protonated Amino and Methylated Derivatives of 2-(2′-Hydroxyphenyl)benzimidazole

Abstract: We studied the excited-state behavior of a family of mono- and diprotonated derivatives of 2-phenylbenzimidazole in different solvents, using steady-state and time-resolved fluorescence spectroscopy. The species investigated were 2-(4'-amino-2'-hydroxyphenyl)benzimidazole (1), the diethylamino analogue 2-(4'-N,N-diethylamino-2'-hydroxyphenyl)benzimidazole (2) and its N-methylated derivative 1-methyl-2-(4'-N,N-diethylamino-2'-hydroxyphenyl)benzimidazole (3). The O-methoxy derivatives of 2 and 3 (2-OMe and 3-OMe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(6 citation statements)
references
References 74 publications
0
6
0
Order By: Relevance
“…46,75−85 It has also been reported that the fluorescence yield decreases significantly upon substitution of the electron acceptor and donor. 46,77,79,80 DHP has strong electron donor and electron acceptor; therefore, its fluorescence decreases significantly. The relatively large quantum yield of the methoxy derivative supports this hypothesis.…”
Section: Resultsmentioning
confidence: 99%
“…46,75−85 It has also been reported that the fluorescence yield decreases significantly upon substitution of the electron acceptor and donor. 46,77,79,80 DHP has strong electron donor and electron acceptor; therefore, its fluorescence decreases significantly. The relatively large quantum yield of the methoxy derivative supports this hypothesis.…”
Section: Resultsmentioning
confidence: 99%
“…The ESIPT-active compounds have been known to undergo deprotonation to yield phenolates and exhibit low energy absorption. [35,36] In order to rule out such possibility, the absorption of 3 has been measured in the presence of a drop of acetic acid. (Figure S5).…”
Section: Resultsmentioning
confidence: 99%
“…These maximum are similar to 2-(m-methylphenyl)benzimidazole, 2-(p-methylphenyl)benzimidazole, 2-(m-methoxyphenyl)benzimidazole, 2-(pmethoxyphenyl)benzimidazole. But the 2-(o-hydroxyphenyl)benzimidazole molecule is observed the specific property in the ground and excited states to describe the keto-enol tautomeric equilibrium through the excited state intramolecular proton transfer [58][59][60][61][62][63][64][65], which property already given in introduction part and theoretical study also done for ketoenol tautomer in solvent effect. The absorption maximum of 2-(o-hydroxyphenyl)benzimidazole was observed at 335, 318 and 295 nm and fluorescence maximum at 355 and 465 nm in DMSO [32].…”
Section: Absorption and Emission Spectral Studymentioning
confidence: 99%